2013
DOI: 10.1002/dc.23052
|View full text |Cite
|
Sign up to set email alerts
|

Subclassification of “atypia of undetermined significance” in thyroid fine‐needle aspirates

Abstract: To identify the subtypes of atypia of undetermined significance (AUS) that confers a different magnitude for the risk of malignancy (RM), thyroid fine-needle aspiration (FNA) cases carrying a diagnosis of "atypical follicular cells" or "follicular lesion" with surgical pathology followup were included in this study. The direct smears of the aspirates were rereviewed and subclassified into four subgroups based on cytomorphology: AUS cannot exclude follicular neoplasm (AUS-FN), AUS cannot exclude Hürthle cell ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
82
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(92 citation statements)
references
References 25 publications
6
82
1
Order By: Relevance
“…Our study shows a slightly higher overall malignancy rate in smears with cytological atypia (78.3%) than in those with only architectural atypia (75.3%). This is in agreement with many previously published studies, in which the estimated risk of malignancy from smears with cytological atypia ranged from 32% [9] to 97% [7] and AUS/FLUS was shown to have a considerably higher risk of malignancy than the other sub-categories. We had only 1 case of AUS with Hürthle cells, which, on resection, was diagnosed as Hürthle cell carcinoma.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Our study shows a slightly higher overall malignancy rate in smears with cytological atypia (78.3%) than in those with only architectural atypia (75.3%). This is in agreement with many previously published studies, in which the estimated risk of malignancy from smears with cytological atypia ranged from 32% [9] to 97% [7] and AUS/FLUS was shown to have a considerably higher risk of malignancy than the other sub-categories. We had only 1 case of AUS with Hürthle cells, which, on resection, was diagnosed as Hürthle cell carcinoma.…”
Section: Discussionsupporting
confidence: 82%
“…Initially, in 2007, the Bethesda guidelines stated that the rate of AUS/FLUS should be < 7% in an ideal setting [15], and that overusage of this category should be minimised as much as possible. However, various studies from tertiary care centres [6, 7, 9, 11, 12, 16] around the world have reported higher rates of AUS of up to 15.8% [17]. The latest 2017 Bethesda guidelines changed the advisable limit of AUS/FLUS to 10% [2].…”
Section: Discussionmentioning
confidence: 99%
“…This could be accomplished using a concise note, Common patterns that would be candidates for subclassifiers include: architectural atypia, nuclear atypia, oncocytic features, and NOS. Several studies have demonstrated that subclassification within the AUS/FLUS category can be effective to better define the ROM, and that nuclear atypia is associated with a higher ROM than other AUS/FLUS patterns [23,24,25,26,27,28]. …”
Section: Specific Issues Pertaining To the Different Diagnostic Categmentioning
confidence: 99%
“…Second, RFNA may not provide a straightforward management decision for a nodule diagnosed as benign by RFNA because the false negative rate of a benign diagnosis by RFNA in nodules initially diagnosed as AUS/FLUS may be higher than that in a single benign diagnosis [7,8]. Thyroid nodules with AUS/FLUS diagnosis include various pathologies, and recent studies [4,9,10,11,12,13,14,15] demonstrate that subcategory nodules showing nuclear atypia (NA) have a higher malignancy risk than other subcategory nodules showing architectural or other atypia, which might require a different management strategy. Although several recent studies [16,17,18,19,20,21,22] have suggested the potential utility of core needle biopsy (CNB) in the management of AUS/FLUS or indeterminate nodules, the role of CNB has not been established and its utility has been little investigated for each subcategory of AUS/FLUS nodules [22].…”
Section: Introductionmentioning
confidence: 99%